FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU MAKAN REMAJA PUTRI DALAM PENCEGAHAN ANEMIA DI WILAYAH KERJA PUSKESMAS NGEMPLAK SIMONGAN - Setyowati, Nanik Dewi; Riyanti, Emmy; Indraswari, Ratih (Jurnal Kesehatan Masyarakat (e-Journal), 2017)
Anemia is one of the causes of maternal mortality rate due to bleeding in pregnant women. Female are very vulnerable group of iron deficiency anemia. The main factors that cause anemia are inadequate intake of iron in the body. This study aimed to determine the factors associated with eating behavior in preventing anemia, used descriptive analytics with cross sectional approach. The study population was females who had anemia. Sampling withÂ  total population of 52 respondents. The results showed that most of respondents had poor eating behaviour (69.2%), late adolescence 17-19 years (46,2%),low education (51,9%), low family income (57,7%), the number of family members small and large family (50%), history of disease (46,2%), normal nutritional status (61,5%), poor knowledge (59,6%), good attitude (51,9%), positive perception of self-image(55,8%), good information exposure (73,1%), good access health services (84.6%), motherÂ  support (51,9%), supportless friend (53,8%), health workers support (61,5%). The results of chi-square testshowed the relationship between education (p=0,026), family income (p=0,049), history of disease (p = 0,022), knowledge (p=0,016), mother support (p=0,026) with the eating behavior in preventing anemia. While the variable age (p=0,303), number of family members (p=0,229), nutritional status (p=0,476), attitude (0.677), the perception of self-image (p= 0,245), exposure of information (p=0,346), access to health services (p=0,472), the support of friends (p=0,817), and health workers support (p=0,924) had not related to eating behavior in preventing anemia. It is suggested to females to improve eating behavior to prevent anemia.